2019
DOI: 10.3390/su11071845
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Research on Remote Sensing Monitoring of Grassland Degradation: A Case Study in the Three-River Source Region, China

Abstract: In this study, we proposed climate use efficiency (CUE), a new index in monitoring grassland ecosystem function, to mitigate the disturbance of climate fluctuation. A comprehensive evaluation index (EI), combining with actual vegetation net primary productivity (NPP), CUE, vegetation coverage, and surface bareness, was constructed for the dynamic remote sensing monitoring of grassland degradation/restoration on a regional scale. By using this index, the grassland degradation/restoration in the Three-River Sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Related studies have also shown similar conclusions, such as Zhang et al used Carnegie-Ames-Stanford to estimate the changing trend of vegetation NPP in TRSR from 1982 to 2012, and the results showed that the average NPP increased in 31 years [33]. Zhang et al found that the Yellow River source grassland showed a recovery trend from 2001 to 2016, and NPP increased significantly [34]. Tang et al used machine learning to simulate the temporal and spatial trend of aboveground biomass (AGB) in the Yellow River source grassland from 2001 to 2020, and the results showed that 69.51% of the grassland AGB showed an upward trend [35].…”
Section: Discussionmentioning
confidence: 56%
“…Related studies have also shown similar conclusions, such as Zhang et al used Carnegie-Ames-Stanford to estimate the changing trend of vegetation NPP in TRSR from 1982 to 2012, and the results showed that the average NPP increased in 31 years [33]. Zhang et al found that the Yellow River source grassland showed a recovery trend from 2001 to 2016, and NPP increased significantly [34]. Tang et al used machine learning to simulate the temporal and spatial trend of aboveground biomass (AGB) in the Yellow River source grassland from 2001 to 2020, and the results showed that 69.51% of the grassland AGB showed an upward trend [35].…”
Section: Discussionmentioning
confidence: 56%
“…A feature space proposed in [41] for monitoring desertification degree of semiarid grasslands was constructed by MSAVI and surface albedo, which generated a new index called the semiarid steppe desertification index. Zhang et al [42] took the disturbance of climate fluctuations into account so that a new index, climate utilization efficiency (CUE), was constructed based on NPP to represent this disturbance. Then, CUE, NPP, FVC, and surface bareness were processed by PCA to further build a new comprehensive index for monitoring the grassland degradation in the Three-River Source Region of China.…”
Section: Grassland Degradation Monitoringmentioning
confidence: 99%
“…In addition, for different research purposes, other indices such as the land surface water index (LSWI) and some red-edge indices have been fully utilized [39,40]. In some studies [41][42][43], researchers can even customize some new indices depending on the characteristics of grasslands under study. In [44], Xue and Su detailed the spectral characteristics of vegetation and summarized the development of over 100 vegetation indices and their specific applicability and representation under different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The indicators to evaluate grassland vegetation dynamic by remote sensing technology mainly include the normalized difference vegetation index (NDVI), enhanced vegetation index (EVI), vegetation coverage (F v ), and net primary productivity (NPP) [6][7][8]. Some recent studies have proposed ground bareness (F b ) as another important parameter of global land cover change [9,10]. As an opposite concept of F v , F b contains the attribute of surface reflectivity and temperature information of grassland vegetation rather than a complementary set of coverage.…”
Section: Introductionmentioning
confidence: 99%